The finite part of divergent integrals with logarithmic factors - Latt, Kaido (Mathematical Modelling and Analysis, 2011)
The concepts of the finite part (f.p.) and analytic finite part (a.f.p.) of divergent integrals are defined in the situation where the singular function in the integral has a logarithmic factor. The change of variables in f.p.- and a.f.p-integrals is examined.